Recognition of Anions - Mingos, David Michael P. (Springer, 2017)
Structure and Bonding is a publication which uniquely bridges the journal and book format. Organized into topical volumes, the series publishes in depth and critical reviews on all topics concerning structure and bonding. With over 50 years of history, the series has developed from covering theoretical methods for simple molecules to more complex systems.